2021
DOI: 10.1016/j.numecd.2021.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased hemoglobin A1c level associates with low left atrial appendage flow velocity in patients of atrial fibrillation

Abstract: Background and aims: High hemoglobin A1c (HbAlc) level is associated with increased cardiovascular disease risk and thromboembolic events [1]. The study sought to explored the association between HbAlc and left atrial appendage flow velocity (LAAV) among non-valvular atrial fibrillation (AF) patients. Methods and results: A total of 249 consecutive non-valvular AF patients who underwent transesophageal echocardiography (TEE) were divided into two subgroups according to the median of LAAV level (<45 cm/s, !45 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…We also showed that LAAFV is related to BNP concentration, which is in agreement with previous studies showing that BNP concentration is significantly inversely correlated with LAAFV in patients with AF [ 20 ]. In this study, we found that the persistent AF decreased the risk of decreased LAAFV in multivariate logistics analysis, which was opposite to the results of the linear analysis and previous study [ 27 ]. The paradoxical results were mainly caused by the cutoff value of LAAFV we chose.…”
Section: Discussioncontrasting
confidence: 99%
“…We also showed that LAAFV is related to BNP concentration, which is in agreement with previous studies showing that BNP concentration is significantly inversely correlated with LAAFV in patients with AF [ 20 ]. In this study, we found that the persistent AF decreased the risk of decreased LAAFV in multivariate logistics analysis, which was opposite to the results of the linear analysis and previous study [ 27 ]. The paradoxical results were mainly caused by the cutoff value of LAAFV we chose.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior studies did not have a uni ed cutoff for low LAA ow velocity, but we all found that non-paroxysmal AF and a larger LAD are linked to an increased rate of reduced LAA ow velocity. [14][15][16] Many previous studies have also found that non-paroxysmal AF and a larger LAD are also associated with left atrial appendage thrombus or ESC formation. We speculate that the reduced LAA ow velocity may play a vital part in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LAA ow velocity has been used as surrogates of LA reservoir and contractile function Several studies have identi ed risk factors associated with decreased LAA ow velocity, including AF type, older age, heart failure, hemoglobin A1c, female sex, brain natriuretic peptide, and LA or LAA anatomy. [11][12][13][14][15][16] However, there are currently no available models to predict LAA ow velocity. Therefore, the purpose of this research was to explore clinical, laboratory, and echocardiographic risk factors for reduced LAA ow velocity in patients with AF and to design a nomogram for AF patients.…”
Section: Introductionmentioning
confidence: 99%